THE PHENOMENON OF GLOBALIZATION AND ITS INFLUENCE ON THE TRAINING OF MANAGERS - Кінаш , Ірина Петрівна; Берлоус, Марія (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2024)
The purpose of the article is to study the concept of "globalization" taking into account the historical aspect of the manifestation of this phenomenon, as well as to clarify the impact of globalization on the training of specialists, in particular managers. It was found that globalization, as a phenomenon, along with political, economic, social, informational, financial, investment, migration and other spheres of human activity, also affects the training of specialists. The historical perspective of the concept of "globalization" is presented. It is established that the context of globalization can be traced in the works of ancient philosophers and researchers. Active use of the term "globalization" in scientific discourse was observed in the second half of the 20th century. The reason for this was the active integration of world markets, the growth of international trade and financial transactions. It has been established that the topic of globalization has now turned into a dominant one. The result of globalization is the formation of a single production and consumer space with agreed rules of interaction, exchange of goods, services, capital, ideas, values, etc. A manifestation of globalization is also observed in social processes. The social conditioning of such a phenomenon is connected with the development of society, which forms the education system as a complex and multidimensional phenomenon. Society forms the educational system, determines the structure, quality, availability. In turn, education affects the development of society and shapes it. Since UNESCO announced the 21st century of education, there is a need to take into account the influence of globalization during the training of specialists, in particular managers. Characteristic features of globalization manifested in education are determined. The effects of globalization on the training of managers are demonstrated. The consequence of globalization is: unification of knowledge, expanding the geography of sales of educational services, striving to achieve high quality education, expanding international cooperation, strengthening the role of international legal regulation of education, intensifying competition, diversifying forms of education.